2020
DOI: 10.18502/ijaai.v19i1.2421
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effects of Curcumin on Transforming Growth Factor-β-mediated Non-Smad Signaling Pathway, Oxidative Stress, and Pro‐inflammatory Cytokines Production with Human Vascular Smooth Muscle Cells

Abstract: Transforming growth factor-β (TGF-β) induces pro-inflammatory cytokines expression including interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) and these cytokines are associated with the development of atherosclerosis. Curcumin has anti-atherogenic effects and anti-inflammatory properties in the vascular wall, but the relative mechanisms are almost unknown. In the present study, we investigate the effect of curcumin on modulating the pro-inflammatory action of TGF-β in human vascular smooth muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Cisplatin-induced DNA damage triggers various signal transduction pathways that can induce the apoptosis mechanism in cancer cells ( 4 , 5 ). Despite cisplatin’s initial therapeutic success, its use can typically limit due to its toxicity in normal cells and resistance of the tumor cells to cisplatin-based chemotherapy, which leads to therapeutic failure ( 6 ). The major toxicities associated with cisplatin overdose include kidney damage (nephrotoxicity), neuropathy, bone marrow suppression and hearing problems (ototoxicity) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin-induced DNA damage triggers various signal transduction pathways that can induce the apoptosis mechanism in cancer cells ( 4 , 5 ). Despite cisplatin’s initial therapeutic success, its use can typically limit due to its toxicity in normal cells and resistance of the tumor cells to cisplatin-based chemotherapy, which leads to therapeutic failure ( 6 ). The major toxicities associated with cisplatin overdose include kidney damage (nephrotoxicity), neuropathy, bone marrow suppression and hearing problems (ototoxicity) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon suggests a probable pathogenic brain disease mechanism mediated by immune responses. 31,32,33 Similarly, the previous study displayed that IgG uptake in the rat neurons was related to eosinophilia and degenerative ultrastructural alteration. It could be indicated that IgG leakage is associated with neuronal impairment and might be a pathogenic mechanism in epileptogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…Curcumin inhibits ROS generation, limits lipid peroxidation ( Panahi et al, 2018 ), and enhances NO bioavailability ( Goel et al, 2008 ; Li et al, 2019a ). Studies demonstrated that curcumin suppresses ROS production in both animal models and in vitro by inhibiting ROS-related inflammation pathways and cytokines ( Zingg et al, 2013 ), such as ERK1/2 pathway ( Ouyang et al, 2019 ; Zhang et al, 2020a ), the high-mobility-group protein B1(HMGB1)- toll-like receptor (TLRS)-NF-κB pathway ( Lv et al, 2020 ), COX-2 ( Lee et al, 2020 ), and others ( Shi et al, 2017 ; Saji et al, 2018 ; Asadi et al, 2020 ), preventing endothelial dysfunction and adhesion molecules secretion. Pu et al found that curcumin alleviated ROS-induced endothelial dysfunction through UCP2 and increased eNOS activity ( Pu et al, 2013 ; Treviño-Saldaña and García-Rivas, 2017 ).…”
Section: Tcm For Treatment Of Atherosclerosis Targeting Oxidative Stressmentioning
confidence: 99%